An innovative approach to activity based travel demand modelling - Vuk, Goran (Proceedings from the Annual Transport Conference at Aalborg University, 2011)
The Danish Strategic Research Council for Transport funded the ACTUM project, Analysis of activity based travel chains and sustainable mobility, in November 2010 with million DKK 21,5. The project assembles a large number of research centres across different fields of transport-related research, both national and international. One of the major tasks in this 5-year project is to develop the European fist operational activity based traffic model. The model is called COMPAS – COpenhagen Model for Person Activity Scheduling, and it is aimed that this model will succeed the OTM model, which is a tour based model for the Greater Copenhagen Area. The purpose of the article is to describe the basic ideas behind the COMPAS model. We start with some theory in chapter 1. Chapter 2 describes data to be completed within the ACTUM project, while chapter 3 describes a proposed structure of the COMPAS model. Conclusions and further work are presented in the final chapter.